SIFAT PEMESINAN BEBERAPA JENIS KAYU DARI DAERAH KALIMANTAN BARAT DAN JAWA BARAT - Osly Rachman; Jamal Balfas (Pusat Penelitian dan Pengembangan Hasil Hutan, 1989)
Machining properties of 16 wood species from West Kalimantan and West Java has been identified using the modified ASTM D-1666 which was described in the Forest Products Research Institute Report No. 160 (1982). The samples (25 pieces/species) were dried to equilibrium moisture content condition (15 to 18% of MC). The machining properties tested are planing, shaping, boring, turning and sanding.Seven species that have good to very good machining properties are kenari I, kenari II, kemayau, belangeran, ki sampang, ki endog and surian bawang. The best machining properties, however, were found on johar, gadog and putat. Whereas the other species are good or very good in some properties and fair or even poor in others,